HUBUNGAN PENGETAHUAN AKSEPTOR TENTANG KONTRASEPSI PIL ORAL KOMBINASI DENGAN KEPATUHAN DALAM MENGKONSUMSI PIL KB DI WILAYAH DESA MARGASANA KECAMATAN JATILAWANG TAHUN 2012 - Prasetyawati, Anna; Suryandari, Artathi Eka; Retnowati, Misrina (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2012)
One of effective contraception chosen by mother is combined oral contraceptive. Family planning program is not too success. It happens caused by mother knowledge and other factors. For having positive attitude about family planning needed good knowledge so obidience to lead family planning increase and also do family planning oral pill combination. For knowing relationship among knowledge acceptor about combined oral contraceptive with compliance in consuming oral pill combination at Margasana village 2012. This research was descriptive correlation research used cross sectional design. The population was all family planning combined oral contraceptive acceptor. The sample used total sampling, 30 people. The analyze data used Chi square. Knowledge acceptor about combined oral contraceptive mostly in good category, 18 people (60%) and the other 12 people were in bad category. Family planning combined oral contraceptive acceptor mostly in obedient category was 16 people (53,3%) and the other 14 people (46,76%) were in disobedience category. There was a significant relation among knowledge acceptor about combined oral contraceptive with obedience in consuming combined oral contraceptive at Margasana village Jatilawang district 2012 (p=0,011). The research showed a significant relation among knowledge acceptor about combined oral contraceptive with obedience in consuming oral pill combination. Family planning acceptors should try to improve their knowledge about combined oral contraceptive so it can prevent unintended pregnancy caused by disobedience in consuming family planning pill everyday and according use.   Keywords       : Knowledge, Obedience, Combined Oral Contraceptive